From the Battlefield to the Silver Screen: How the Failed Makin Atoll Raid was Spun into a Success, 1943-1943 - Duerst, Logan P. (My University, 2017)
A day after the attack on Pearl Harbor, the United States of America entered into World War II, declaring war on the Empire of Japan. Although not prepared to make any significant military counterattack on the vast Japanese Pacific Empire, the American military, and people, wanted retribution for the attacks on Pearl Harbor on December 7, 1941. Built to strike quickly and effectively, 211 marines comprised the 2nd Raider Battalion. On August 17, 1942 the 2nd Raider Battalion was tasked with raiding the Japanese military garrison on the Makin Atoll, deep behind Japanese controlled territory. The raid was far from a success, with few to no objectives accomplished, along with 18 marines killed and 12 missing in action. However, in the aftermath of the failed mission success was found, or rather created as the film ’Gung Ho!’: The Story of Carlson’s Makin Island Raiders was released to theaters in December of 1943. A highly praised movie at the time, this paper will examine the relationship and varied success levels between the raid and the subsequent film.
Keywords: World War, 1939-1945 --Amphibious operations; Makin Atoll, Battle of, Kiribati, 1943; Pearl Harbor (Hawaii), Attack on, 1941